Ecosystem history of a tropical reservoir revealed by metals, nutrients and photosynthetic pigments preserved in sediments - de Oliveira Soares Silva Mizael, Juliana [UNESP]; Cardoso-Silva, Sheila [UNESP]; Frascareli, Daniele [UNESP]; Pompêo, Marcelo Luiz Martins; Moschini-Carlos, Viviane [UNESP] (Elsevier, 2020)
Many studies have found evidence of processes of eutrophication and contamination by metals in reservoirs worldwide. The present work discusses the history of changes associated with anthropic impacts in a tropical reservoir (São Paulo, Brazil), using the analysis of metals, nutrients, and pigments in sediment cores. Three cores were obtained in the dam area of the reservoir. One was used for determination of grain size, organic matter (OM), total phosphorus (TP), and total nitrogen (TN). The second core was used for 210Pb dating and analysis of metals (Cr, Cu, Ni, Pb, Zn, Mn, Al, and Fe). The third core was used for analysis of the pigments chlorophyll-a (Chl-a), beta-carotene (Bet), fucoxanthin (Fuc), lutein (Lut), and zeaxanthin (Zea). For the metals, no significant signs of contamination or enrichment were observed. Only Mn presented an increase over time, which was suggestive of increased effluent inflows and erosion processes. Sedimentation rates (SR) tended to increase from the 1990s onwards, which appeared to be due to eutrophication and changes related to land use and occupation in the watershed. In the case of the pigments, there were increases mainly of lutein and zeaxanthin, indicating the presence of Chlorophyta and Cyanobacteria, respectively, associated with eutrophication. Principal component analysis (PCA) was performed, with the first component (PC1) for the deepest layers indicating that they were characterized by the presence of the metals Al, Pb, and Zn (score of −0.89), together with Fe and sand (score of −0.81), which did not indicate enrichment or any significant contamination, hence representing a condition of lower impacts. On the other hand, the upper layers, representing the period from the 1990s onwards, were characterized by variables in PC1 that could be associated with increase of the trophic level (such as Chl-a, score of 0.81) and increased erosive processes (such as SR, score of 0.79). This study helps to address the lack of long-term data for the Broa reservoir and provides information relevant to trophic reconstruction studies of reservoirs using the analysis of photosynthetic pigments. This research helps in identifying recovery targets and could be applied in other contexts, since the impact of eutrophication processes on water bodies is a global scale problem.
Keywords: Broa reservoir; Ecological risk; Eutrophication; Lutein; Paleolimnology; Zeaxanthin